(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2020)
The Editorial Board of the Latin American Journal of Sedimentology and Basin Analysis would like to express its gratitude to the colleagues who acted as reviewers of the manuscripts processed during the period 2018-2020.